Pengaruh Dukungan Sosial terhadap Stress Kerja pada Anggota Polri di Polres Karanganyar - Annisa Dian Kharisma (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The police are a civil intermediary who regulates order and law. The function of the police is a state government function in the field of maintaining and securing public order. Therefore, the police's job is quite difficult, the challenges and pressure at work cause work stress. Social support from various parties is very effective in reducing work stress for police officers. This research aims to determine the effect of social support on work stress among police officers at the Karanganyar Police Station. The hypothesis proposed is that there is an influence between social support and work stress among police officers at the Karanganyar Police Station. This research uses quantitative methods with data collection techniques using questionnaires distributed to members. The conclusion of this research is that there is a significant influence between social support on work stress among police officers at Karanganyar Police. The higher the level of social support, the lower the level of work stress and conversely, if the social support is lower, the level of work stress will be higher. Therefore, social support can reduce or prevent work stress.